The structural-semantic field of dichotomy “one’s own – alien” in the English language world picture - Shepel, Yuri; Panchenko, Olena; Zirka, Vira; Fedina, Olena (Linguistics and Culture Review, 2021)
The article deals with the study of the value content of the dichotomy “one’s own – alien” in the English linguistic world picture. The novelty of the proposed study lies in the fact that the researcher does not proceed from a predetermined model of description construction, but the model is deducted from the material researched. The lexical units that can act as direct objectifies (keywords, cohyponyms and typical verbalizers) of the concepts “one’s own – alien” which are based on the idea of a stereotypical situation that explains the value content of the opposition in the English language consciousness, are analysed. The modern linguistic interpretation of the conceptual opposition “one’s own – alien” and verification of the research results is performed on the basis of analysis of dictionaries and media texts to compare associations with the concepts “one’s own – alien” of English speakers, to clarify the links of language units – representatives of the concepts “one’s own – alien” with the structures of knowledge about their denotations and with extraverbal reality, highlighting their mental characteristics and principles of functioning in English.